A preliminary study on multi-level biomarkers response of the tropical oyster Crassostrea brasiliana to exposure to the antifouling biocide DCOIT - Campos, Bruno Galvão de [UNESP]; Fontes, Mayana Karoline [UNESP]; Gusso-Choueri, Paloma Kachel; Marinsek, Gabriela Pustiglione [UNESP]; Nobre, Caio Rodrigues [UNESP]; Moreno, Beatriz Barbosa; Abreu, Fiamma Eugenia Lemos; Fillmann, Gilberto; de Britto Mari, Renata [UNESP]; Abessa, Denis Moledo de Souza [UNESP] (Elsevier, 2022)
This study investigated the sublethal effects of environmentally relevant concentrations of DCOIT on the neotropical oyster Crassostrea brasiliana. Gills and digestive glands of animals exposed to increasing concentrations of DCOIT were analyzed for biochemical, cellular, and histopathological responses. Exposure to DCOIT (0.2 to 151 μg L−1) for 120 h triggered oxidative stress in both tissues (through the modulation of GPX, GST, GSH and GR), which led to damage of membrane lipids (increase of LPO and reduction of the NRRT). DCOIT increased histopathological pathologies in gills, such as necrosis, lymphocyte infiltration and epithelial desquamation. This study showed that short term exposure to environmental concentrations of DCOIT causes negative effects on C. brasiliana at biochemical, physiological, and histological levels. Therefore, the use of DCOIT as a booster biocide in antifouling paints should be further assessed, as it may cause environmental hazards to marine organisms.
Keywords: Bivalve; Environmental hazard; Histopathology; Neutral red; Sea-nine; Toxicity